Editorial - A Missing Link: The Influence of Societal Beliefs on Integration among the World's Emerging Population of Persons with Disabilities (PWDs) - Michel D. Landry (World Health & Population, 2009)
More than 30 years ago, the Declaration of Alma-Ata reported that "an acceptable level of health for all the people of the world by the year 2000" was possible, and urgently expressed the need for collective action to protect and promote health worldwide. At the time, the United Nations boldly challenged the global community to eliminate the inequality in the health status of people across developed and developing nations (WHO and UNICEF 1978). In the decades that have passed since Alma-Ata, the goal of health as a basic human right to which all individuals are entitled has remained largely unfulfilled.